Trypanosoma cruzi Evades the Complement System as an Efficient Strategy to Survive in the Mammalian Host: The Specific Roles of Host/Parasite Molecules and Trypanosoma cruzi Calreticulin - Ramírez-Toloza, Galia; Ferreira, Arturo (Frontiers in Microbiology, 2017)
American Trypanosomiasis is an important neglected reemerging tropical parasitism, infecting about 8 million people worldwide. Its agent, Trypanosoma cruzi, exhibits multiple mechanisms to evade the host immune response and infect host cells. An important immune evasion strategy of T. cruzi infective stages is its capacity to inhibit the complement system activation on the parasite surface, avoiding opsonizing, immune stimulating and lytic effects. Epimastigotes, the non-infective form of the parasite, present in triatomine arthropod vectors, are highly susceptible to complement-mediated lysis while trypomastigotes, the infective form, present in host bloodstream, are resistant. Thus T. cruzi susceptibility to complement varies depending on the parasite stage (amastigote, trypomastigotes or epimastigote) and on the T. cruzi strain. To avoid complement-mediated lysis, T. cruzi trypomastigotes express on the parasite surface a variety of complement regulatory proteins, such as glycoprotein 58/68 (gp58/68), T. cruzi complement regulatory protein (TcCRP), trypomastigote decay-accelerating factor (T-DAF), C2 receptor inhibitor trispanning (CRIT) and T. cruzi calreticulin (TcCRT). Alternatively, or concomitantly, the parasite captures components with complement regulatory activity from the host bloodstream, such as factor H (FH) and plasma membrane-derived vesicles (PMVs). All these proteins inhibit different steps of the classical (CP), alternative (AP) or lectin pathways (LP). Thus, TcCRP inhibits the CP C3 convertase assembling, gp58/68 inhibits the AP C3 convertase, T-DAF interferes with the CP and AP convertases assembling, TcCRT inhibits the CP and LP, CRIT confers ability to resist the CP and LP, FH is used by trypomastigotes to inhibit the AP convertases and PMVs inhibit the CP and LP C3 convertases. Many of these proteins have similar molecular inhibitory mechanisms. Our laboratory has contributed to elucidate the role of TcCRT in the host-parasite interplay. Thus, we have proposed that TcCRT is a pleiotropic molecule, present not only in the parasite endoplasmic reticulum, but also on the trypomastigote surface, participating in key processes to establish T. cruzi infection, such as inhibition of the complement system and serving as an important virulence factor. Additionally, TcCRT interaction with key complement components, participates as an anti-angiogenic and anti-tumor molecule, inhibiting at least in important part, tumor growth in infected animals.